2016
DOI: 10.1037/xge0000213
|View full text |Cite
|
Sign up to set email alerts
|

Distractibility is a function of engagement, not task difficulty: Evidence from a new oculomotor capture paradigm.

Abstract: It has been shown that when humans require a brief moment of concentration or mental effort, they tend to avert their gaze away from the attended location (or even blink). Similarly, participants tend to miss unexpected events when they are highly focused on a task. We present an engagement theory of distractibility that is meant to capture the relationship between participants' engagement in a task and reduction in sensitivity to new sensory events in a broad range of situations. In a series of experiments, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 92 publications
4
53
0
Order By: Relevance
“…For example, reducing the perceptual discriminability of to-be-remembered material eliminates the disruption that an unexpected deviant sound confers on the ordered recall of sequences of visually-presented items (Hughes et al, 2013). It was argued in Hughes et al (2013) that perceptual difficulty increased task-encoding load and eliminated the disruptive effect of the unexpected deviant sound by supporting an upward shift in focal task-engagement through a top-down mechanism (for a similar notion, see Buetti &Lleras, 2016, andFaber et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…For example, reducing the perceptual discriminability of to-be-remembered material eliminates the disruption that an unexpected deviant sound confers on the ordered recall of sequences of visually-presented items (Hughes et al, 2013). It was argued in Hughes et al (2013) that perceptual difficulty increased task-encoding load and eliminated the disruptive effect of the unexpected deviant sound by supporting an upward shift in focal task-engagement through a top-down mechanism (for a similar notion, see Buetti &Lleras, 2016, andFaber et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Another possibility is that by engaging participants in an auditory task and incentivizing performance on that task by requesting the AWM response first, participants may have disengaged from the saccade task. For example, Buetti and Lleras (2016) showed that engagement in an auditory task leads to less distraction by visual events. Finally, it is also possible participants translated their response to the saccade task into a verbal code (e.g., "forwards"), which was then disrupted by the letter memory task.…”
Section: Experiments 6a Vs 6bmentioning
confidence: 99%
“…Via written instruction, we informed participants that the pictures were irrelevant and that they should maintain gaze on the screen throughout the experiment because eyes were only tracked within the area of the screen. This approach to use attentional capture by distractor images during IDC as index of attentional focus was previously employed by Buetti and Lleras (2016). At the end of each trial, participants were prompted to type in their best and second-best idea.…”
Section: Procedures and Taskmentioning
confidence: 99%